Exploitation of Simultaneous Alcoholic and Malolactic Fermentation of Incrocio Manzoni, a Traditional Italian White Wine - Guzzon, R.; Moser, S.; Davide, S.; Villegas, T.R.; Malacarne, M.; Larcher, R.; Nardi, T.; Vagnoli, P.; Krieger-Weber, S. (South African Journal of Enology and Viticulture, 2016)
Malolactic fermentation (MLF) is a key feature in the production of high-quality wines. Its evolution is not always guaranteed, especially in white wine, due to certain limiting factors (low pH, sulphur dioxide, low temperature) acting against malolactic bacteria. The inoculation of grape must with bacteria is an alternative approach to the management of oenological fermentation, favouring the survival of bacteria due to the absence of ethanol or sulphur dioxide – toxic compounds made by yeasts in the first stages of winemaking. We compared the activity of two strains of Oenococcus oeni during MLF in wines made from an emerging white grape variety, native to north-eastern Italy, namely Incrocio Manzoni. Different winemaking protocols were assayed, comparing sequential or simultaneous inoculation of microbial starters. The monitoring of bacterial viability through fermentations and a comprehensive characterisation of the volatile profile of the wines were achieved by advanced analytical approaches, flow cytometry and GC-MS respectively. According to the preliminary hypothesis, the chemical composition of the grape must was characterised by high acidity, which represented a serious barrier to bacterial development. Simultaneous inoculation of the two O. oeni strains ensured a regular evolution of MLF. Some differences were highlighted, both in terms of fermentation kinetics and the aromatic profile of the wines obtained, in relation to the strain of lactic bacteria. The work provides an exhaustive overview of the opportunities and risks related to different wine fermentation approaches in order to enhance the quality of white wines made from “new” or “local” wine grapes.